The Effect of Knowledge of Mothers Assisted by Cadres during Pregnancy on the Incidence of Low Birth Weight - Rasyid, Puspita Sukmawaty; Claudia, Juli Gladis; Agustini, Rahma Dewi; Nurhidayah, Nurhidayah; Yanti, Febri Dwi; Luawo, Herman Priyono (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Every pregnancy carries risks to the quality of birth outcomes, such as low birth weight (LBW). Interventions such as increased maternal knowledge, supervision, and intensive assistance are required, which can be performed by health cadres. The study aimed to examine the impact of knowledge on the incidence of LBW in pregnant women accompanied/assisted by cadres during pregnancy. This method combines descriptive research with a quasi-experiment. The study included 30 pregnant women who fulfilled the following criteria: single pregnancy, 30 weeks gestation, not a high-risk pregnancy, and no comorbidities. The study lasted three months, and the independent variable was the knowledge of pregnant women assisted by cadres, while the dependent variable was the incidence of LBW. Pregnant women's questionnaires and observation sheets were employed as instruments. T-Test and Yates' Correction were utilized during data analysis. The findings revealed a p-value of 0.031 increase in knowledge of pregnant women before and after being assisted by cadres during pregnancy, and the incidence of LBW was 3 cases (10%). With a p-value of 0.041, the results of Yates' Correction statistical test revealed that knowledge of pregnant women assisted by cadres is one of the determinants of the occurrence of LBW. It is critical to increase cadre involvement and role in assisting pregnant women.